Training systems and labor mobility: A comparison between Germany and Sweden - Tomas Korpi; Antje Mertens (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
The impact of general and specific training on income and mobility is an important issue for the discussion around human capital as well as the design of educational systems. Using data from two retrospective life-history surveys this paper examines the impact of more general school-based vocational training (Sweden) and more specific apprenticeship training (Germany) on inter-firm, inter-occupational, and inter-industrial mobility. The results show that workers with a school-based vocational degree move more frequently between occupations, while no difference in firm and industrial mobility can be discerned.
urn:nbn:de:kobv:11-10048770
Keywords: 330